2020
DOI: 10.1109/tevc.2019.2940828
|View full text |Cite
|
Sign up to set email alerts
|

Landscape-Aware Performance Prediction for Evolutionary Multiobjective Optimization

Abstract: We expose and contrast the impact of landscape characteristics on the performance of search heuristics for black-box multi-objective combinatorial optimization problems. A sound and concise summary of features characterizing the structure of an arbitrary problem instance is identified and related to the expected performance of global and local dominancebased multi-objective optimization algorithms. We provide a critical review of existing features tailored to multi-objective combinatorial optimization problems… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
54
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 56 publications
(58 citation statements)
references
References 47 publications
0
54
0
Order By: Relevance
“…In terms of parameters, NSGA-II, IBEA and MOEA/D all use a population of size of 100, an exchange mutation with a rate of 0.2, and a partially-mapped crossover [10] with a rate of 0.95. Preliminary experiments revealed that using the partiallymapped crossover allows the search process to reach better quality in more than 90% of the cases, compared against the 2-point crossover used in a previous setting [15]. All the algorithms stop after 1 000 000 evaluations.…”
Section: Algorithms Setting and Search Performancementioning
confidence: 99%
See 4 more Smart Citations
“…In terms of parameters, NSGA-II, IBEA and MOEA/D all use a population of size of 100, an exchange mutation with a rate of 0.2, and a partially-mapped crossover [10] with a rate of 0.95. Preliminary experiments revealed that using the partiallymapped crossover allows the search process to reach better quality in more than 90% of the cases, compared against the 2-point crossover used in a previous setting [15]. All the algorithms stop after 1 000 000 evaluations.…”
Section: Algorithms Setting and Search Performancementioning
confidence: 99%
“…We start our analysis by characterizing mQAP instances with relevant features from the literature. We rely on the multi-objective landscape features introduced in [15], and particularly on local features, based on sampling, that do not require any prior knowledge about the solution space enumeration and/or the Pareto set. We start by recalling their definition.…”
Section: Feature-based Landscape Analysismentioning
confidence: 99%
See 3 more Smart Citations